From Morality to the Body : Questioning the Reorientation of Rape in the Indonesian Criminal Code - Zulfiqar Bhisma Putra Rozi; Kartika Youri Widodo (Peradaban Journal of Law and Society, 2026)
This study examines the paradigm shift in the legal classification of rape under the Indonesian Criminal Code, particularly its reclassification from a crime against morality under Article 285 of the former Criminal Code to a crime against the body under Article 473 of the new Criminal Code. It investigates whether this reclassification is theoretically justified and examines its implications for the legal protection of rape victims. Employing normative legal research, the study combines statutory, conceptual, and comparative approaches to analyze the formulation of rape in both criminal codes. The findings reveal that although the new classification strengthens the protection of victims by recognizing rape as an offense against bodily interests, it does not fully reflect the normative essence of rape within the Indonesian legal and socio-cultural context. From a conceptual and anthropological perspective, rape constitutes not only a violation of bodily integrity but also an assault on personal dignity, honor, and the moral values upheld by society. Accordingly, classifying rape solely as a crime against the body risks narrowing its legal meaning and overlooking its broader moral and social dimensions. The study therefore argues for a more integrative legal approach that protects both bodily integrity and the victim's moral dignity in the future development of Indonesian criminal law. Penelitian ini mengkaji pergeseran paradigma dalam klasifikasi hukum tindak pidana perkosaan dalam Kitab Undang-Undang Hukum Pidana Indonesia, khususnya perubahan dari tindak pidana terhadap kesusilaan sebagaimana diatur dalam Pasal 285 KUHP Lama menjadi tindak pidana terhadap tubuh sebagaimana diatur dalam Pasal 473 KUHP Baru. Penelitian ini bertujuan untuk mengkaji apakah reklasifikasi tersebut memiliki dasar teoretis yang memadai serta implikasinya terhadap perlindungan hukum bagi korban perkosaan. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan peraturan perundang-undangan, konseptual, dan komparatif untuk menganalisis pengaturan tindak pidana perkosaan dalam kedua kodifikasi tersebut. Hasil penelitian menunjukkan bahwa meskipun klasifikasi baru memperkuat perlindungan korban dengan menempatkan perkosaan sebagai tindak pidana terhadap tubuh, pengaturan tersebut belum sepenuhnya mencerminkan hakikat normatif tindak pidana perkosaan dalam konteks hukum dan sosial budaya Indonesia. Dari perspektif konseptual dan antropologis, perkosaan tidak hanya merupakan pelanggaran terhadap tubuh, tetapi juga merupakan serangan terhadap martabat, kehormatan, dan nilai-nilai moral masyarakat. Oleh karena itu, penggolongan perkosaan semata-mata sebagai tindak pidana terhadap tubuh berpotensi mempersempit makna hukumnya serta mengabaikan dimensi moral dan sosial yang melekat pada tindak pidana tersebut. Penelitian ini merekomendasikan pendekatan hukum yang lebih integratif untuk melindungi integritas tubuh sekaligus martabat korban dalam pengembangan hukum pidana Indonesia.